Temporary Contract Adjustment to a Retailer with a Private Demand Forecast - Nasser, Sherif; Turcic, Danko (Management Science, 2019)
This paper analyzes a setting in which a manufacturer (he) and a retailer (she) face uncertain demand, but the retailer has an information advantage in the form of a private demand forecast. Such information asymmetry causes the manufacturer to incur a hidden information cost. The results show that a manufacturer can leverage his timing advantage to strategically implement a temporary contract adjustment (TCA) mechanism, which allows him to counter his informational disadvantage and either eliminate or reduce the hidden information cost. The manufacturer implements the TCA mechanism by designing the supply contract with two sets of terms: presignal and postsignal. Presignal terms engage the retailer before observing the forecast signal and induce her to decide under high uncertainty. As a result, she overinvests when the forecast signal is low. Postsignal terms engage her after the signal, allowing her to make use of the information and purchase additional stock efficiently based on the forecast signal. This ability to utilize the forecast information allows the manufacturer to set more efficient contract terms. By applying the TCA mechanism to a simple wholesale price contract, the manufacturer can achieve the effect of free, partial information revelation as if he observes a coarse version of the retailer’s private forecast. By applying the TCA mechanism to a (stronger) quantity-transfer menu, the manufacturer can achieve the effect of free, full information revelation (i.e., full information profits) as if he fully observes the same version of the forecast, without the retailer directly sharing her private information. The online appendix is available at https://doi.org/10.1287/mnsc.2017.2942 . This paper was accepted by Juanjuan Zhang, marketing.